ANALYZING THE ROLE OF EMPOWERMENT IN MEDIATING EFFECT OF KNOWLEDGE MANAGEMENT ON OCB - Rita Aryani; Widodo Widodo (UNIVERSITAS INDRAPRASTA PGRI, 2020)
This study analyzes the effect of knowledge management on organizational citizenship behavior (OCB) mediating by empowerment. The research data was collected by a questionnaire through the survey methods toward 375 teachers. Data analysis uses path analysis supported by descriptive statistics. The results show that knowledge management had a significant effect on OCB mediating by empowerment. Thus, the teacher’s OCB can be improved through knowledge management and empowerment. This finding can be discussed as a reference among researchers and practitioners to develop better models of OCB in the future and various contexts of organizations.